Arthroscopy of the Dorsal and Plantar Pouches of the Tarsocrural Joint for the Treatment of Osteochondritis Dissecans in the Horse: Clinical Features and Follow‐Up. Issue 8 (29th September 2016) - James, Oliver; Payne, Richard; Bathe, Andrew; Greet, Tim; Wylie, Claire
Abstract : Objective: To describe the clinical details and pathology within the dorsal and plantar pouches of the tarsocrural joint of a population of horses that underwent arthroscopic surgery for tarsocrural osteochondritis dissecans (OCD). Study Design: Retrospective cohort study. Animals: Horses referred for arthroscopic treatment of tarsocrural OCD between 2005 and 2013 (102 horses; 144 joints). Methods: Case records of all horses that had tarsocrural arthroscopy for OCD at Rossdales Equine Hospital, Newmarket, United Kingdom were included. Cases from 3 ECVS Diplomates were included, 1 of whom routinely examined 70 plantar pouches concurrently with routine dorsal pouch investigation. A structured questionnaire was used to obtain follow‐up data alongside examination of racing records where appropriate. Descriptive data and 95% CI were calculated. Results: Of the 70 joints that had both dorsal and plantar pouches examined, there was cartilage erosion/degeneration in 22 dorsal pouches (31.4%), cartilage wear lines in 32 plantar pouches (45.7%), and fragments were removed at the time of surgery from 7 plantar pouches (10.0%). Of the plantar pouches with wear lines, 18 (25.7%) had no evidence of cartilage abnormalities (separate from the OCD lesion) within the dorsal pouch. From the 102 horses with available follow‐up, 34 horses (66.7%) achieved their intended use postsurgery. Conclusion: Routine plantar pouch investigation is warranted in cases of tarsocrural OCD to provide further information on the health of the joint and allows for removal of fragments from the plantar pouch that may not have been identified by routine diagnostic radiography.